Resting regional brain activity correlates of verbal learning deficit in major depressive disorder. (30th January 2019) - Milak, Matthew S.; Potter, W. Antonio; Pantazatos, Spiro P.; Keilp, John G.; Zanderigo, Francesca; Schain, Martin; Sublette, M. Elizabeth; Oquendo, Maria A.; Malone, Kevin M.; Brandenburg, Holly; Parsey, Ramin V; Mann, J. John
Highlights: Performance of major depressive disorder (MDD) subjects on the Buschke Selective Reminding Task (SRT) is on average 0.5 standard deviation below published normative mean. SRT total recall (TR) score and relative regional cerebral metabolic rate for glucose (rCMRglu) positively correlate in bilateral dorsomedial prefrontal cortex (PFC), dorsolateral PFC, and dorsal anterior cingulate. TR and rCMRglu negatively correlate in bilateral mesiotemporal cortex (MTC) and basal ganglia. rCMRglu in dorsolateral PFC correlates negatively with that in MTC in healthy comparison subjects but not in MDD subjects. Abstract: Memory deficits are reported in major depressive disorder (MDD). Prefrontal cortical and mesiotemporal cortical (MTC)/subcortical regions are involved in the Buschke Selective Reminding Task (SRT), a verbal list-learning task. To determine whether depression-related changes in resting brain metabolism explain (in part) the deficits in SRT performance found in MDD, statistical correlation maps were calculated between SRT total recall score (TR) and relative regional cerebral metabolic rate for glucose (rCMRglu), measured by [ 18 F]-flourodeoxyglucose (FDG) positron emission tomography (PET), in unmedicated, depressed MDD patients ( N = 29 ). Subsequently, to explore hypothesized loss of top-down control in MDD, we compared the correlations between rCMRglu of SRT-relevant regions of the dorsolateral prefrontal cortex (dlPFC) and amygdala in a larger cohort of MDD ( N = 60; 29 inclusive ) versus healthy controls (HC) ( N = 43 ). SRT performance of patients is on average 0.5 standard deviation below published normative mean. TR and rCMRglu positively correlate in bilateral dorsomedial PFC, dlPFC, dorsal anterior cingulate; negatively correlate in bilateral MTC/subcortical regions, and cerebellum. rCMRglu in dlPFC correlates negatively with that in amygdala in HC but not in MDD. Depression-related changes present in FDG-PET measured resting brain activity may be in part responsible for memory deficit found in MDD.